2009
DOI: 10.1002/pi.2714
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanosilica particles on the cure and physical properties of an epoxy thermoset resin

Abstract: Measurements are reported on the cure and physical properties of an epoxy resin created using a functionalised nanosilica filler. The filled bisphenol A epoxy (Nanopox A410) contained 40 wt% silica nanoparticles and was blended with two bisphenol A resins of molecular weights of 355 and 1075 g mol−1, respectively. Cure was achieved using 3,3‐diaminodiphenylsulfone. The functionality of the mixture containing the epoxy nanoparticles was determined using NMR analysis. Cure times showed a progressive decrease wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…For example, at filler content of 30 phr, the T g of epoxy nanocomposite declines to 169°C. The significant drop in T g is unusual (as high as *55°C) since it is quite mild in most cases, as reported in the literature [7,8,17]. Comparatively, 20-phr micron-sized alumina particles do not affect the T g value substantially; the T g of the microcomposite is 221°C, very close to that of the neat epoxy sample.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…For example, at filler content of 30 phr, the T g of epoxy nanocomposite declines to 169°C. The significant drop in T g is unusual (as high as *55°C) since it is quite mild in most cases, as reported in the literature [7,8,17]. Comparatively, 20-phr micron-sized alumina particles do not affect the T g value substantially; the T g of the microcomposite is 221°C, very close to that of the neat epoxy sample.…”
Section: Resultssupporting
confidence: 54%
“…However, it is still uncertain how nanoparticles affect the glass transition behaviors of epoxy resins. In the literature, the glass transition temperatures (T g ) of epoxy resins have been reported to increase [1,[11][12][13], decrease [14][15][16][17][18], not change [19][20][21], or even show non-monotonic trend [22][23][24] as a function of filler content. This reflects the very complicated interactions between filler and resin, depending on numerous factors, such as type of epoxy resin and filler, surface physicochemistry of filler, filler loading, curing degree of epoxy, interfacial characters, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Segundo Pethrick et al [31], matrizes epóxi termorrígidas normalmente têm uma baixa resistência à propagação de trincas, e através da incorporação de uma segunda fase particulada seja ela em escala micro ou nano ou mesmo a combinação das duas pode-se aumentar a resistência mecânica final do compósito. Entretanto, sabe-se que para lidar com as limitações dos polímeros, como sua baixa rigidez e baixa resistência mecânica, partículas inorgânicas podem ser adicionados para aumento da rigidez do polímero [32][33][34].…”
Section: Figura 3: Módulo De Flexão Dos Compósitosunclassified
“…DGEBA cured with 3,3 0 -diaminodiphenyl sulfone (3,3 0 -DDS), tested by Rhoney et al, 26 showed a reduction in gel time with increasing silica levels without much change in the cure profile. The T g , determined by thermomechanical analysis, was lowered from 163 to 146 C at approximately 33 wt % nanosilica.…”
Section: Amine-cured Epoxy Resinsmentioning
confidence: 99%